The Concept of Diploma Thesis Using Design Thinking - Duda, Aneta; Mazur, Piotr (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article substantiates the urgency of the problem in the context of contemporary public challenges, in particular, the improvement of the quality of the provision of educational services for the training of teaching staff. One of these challenges is practically oriented pedagogy, which involves a close combination of theory and practice in a particular socio-cultural situation. In this sense, the need to develop teachers' professional competence, creativity, critical and design thinking is emphasized by the authors. The aim of this article is to present the concept of diploma thesis using the Design Thinking method. The goal of Design Thinking is to create new solutions based on a deep understanding of users' problems and needs. The human-centered design consists of five stages: empathisation, defining the problem, generating the ideas, prototyping and testing. The article is based on the authors' experience of implementing Design Thinking in education. The importance of design thinking in the educational process is stressed, in particular for the effective diagnosis of students' educational needs during the lessons preparation. It is mentioned that educators learning specific methods of work and project thinking could successfully organize lessons or create a school environment that addresses the interests and creative needs of students. The article is written using the practical experience of the authors to introduce design thinking into education. The researchers are convinced of the need to involve young people in the writing of diploma researchers on the development of design thinking, professional creativity. At the same time, it is also important to carry out pedagogical research in a particular field of scientific knowledge, since the scientific and pedagogical community needs experts and theorists in the field of education.